Pilgrimage and procession: temporary gatherings and journeys between the tangible and intangible through the archaeology of South Asia. Issue 2 (15th March 2018) - Davis, Christopher; Coningham, Robin
ABSTRACT: South Asia is home to many of the world's major religions, and over a century of archaeological enquiry has documented the sites associated with these traditions. Although textual scholarship, augmented by art historical and architectural studies of durable remains, has dominated interpretations, recent archaeological studies have begun to redress this balance by contextualizing monuments within their landscapes and engaging with the varied roles that such monuments played in the past. Referencing ethnographic analogy and archaeological visibility of ritual practices, alongside analysis of archaeological and textual evidence, the authors explore the issues faced when identifying and interpreting temporary gatherings at these sites in the past with reference to pilgrimage. Utilizing a broad-spectrum approach through varying time-periods and traditions, they advance potential ways of bridging the gap between intangible practices and tangible evidence, revealing the role of settlements, religious sites and landscapes as routeways and assembly points for pilgrimages and processions.